The Effect of Corporate Governance and Profitability on Social Responsibility - Ramlah Ramlah; Nurlaely Razak; Muhammad Tafsir; Hasyim Mochtar; Djamilah Saleh (P3M STIEM BONGAYA, 2022)
ABSTRACT: This study examines and analyses corporate governance's effect on social responsibility. This research was conducted at PT. Pelabuhan Indonesia IV (Persero) and to test and analyze the impact of profitability on social responsibility. Data collection uses secondary data using a saturated sample technique (census). The population in this study is the financial statements of 10 working areas at PT. Pelabuhan Indonesia IV (Persero), while the sample taken is the number of observations for three years (2018 to 2020). The data obtained were analyzed using multiple linear regression analysis, t-test and the Coefficient of Determination (R²) test, the processing of which was carried out using the SPSS version 23 program. The results showed that the first and second hypotheses proposed were accepted because they showed positive and significant hypothesis test results. This means that corporate governance has a positive and significant effect on corporate social responsibility, and profitability has a positive and significant impact on corporate social responsibility.